2019
DOI: 10.24251/hicss.2019.406
|View full text |Cite
|
Sign up to set email alerts
|

Pushing Open Government Through Social Media

Abstract: E-government aims to enhance the interaction between citizens, business, and government. Recently, the term open government is increasingly used to emphasize the importance of co-creation in governmental issues. In this study, the social media activities of the municipalities of North Rhine-Westphalia, Germany, are investigated with regard to the topic "open government" as one pillar of e-government. The findings show that user interaction is mostly represented through likes and shares and rarely by comments. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 26 publications
0
1
0
Order By: Relevance
“…Others have found that OGD portals situate the government as a data custodian rather than a service provider [13,14]. Although studies have examined policies [13,15], data sources [12,16], theoretical research on data publics [17], efforts to promote OGD portals on social media [18], and the use of these tools by technology-savvy users [19], we found that there is very limited research related to the feedback on the performance of open data portals and the use of this data from user's perspective as they engage in local decision-making processes.…”
Section: The Value Of Ogdmentioning
confidence: 99%
“…Others have found that OGD portals situate the government as a data custodian rather than a service provider [13,14]. Although studies have examined policies [13,15], data sources [12,16], theoretical research on data publics [17], efforts to promote OGD portals on social media [18], and the use of these tools by technology-savvy users [19], we found that there is very limited research related to the feedback on the performance of open data portals and the use of this data from user's perspective as they engage in local decision-making processes.…”
Section: The Value Of Ogdmentioning
confidence: 99%